Non-vernalization Flowering and Seed Set of Cabbage Induced by Grafting Onto Radish Rootstocks - Motoki, Ko; Kinoshita, Yu; Hosokawa, Munetaka (Frontiers in Plant Science, 2019)
Cabbage (Brassica oleracea var. capitata) requires a long-term low-temperature exposure for floral induction, causing a delay in the breeding cycle. The objective of this study is to develop a method to induce flowering in cabbage without low-temperature treatment, using a grafting method. We conducted grafting experiments using two flower-induced Chinese kale cultivars (B. oleracea var. alboglabra) and seven radish cultivars/accessions as rootstocks and investigated the flowering response of grafted cabbage scions without low-temperature treatment. “Watanabe-seiko No.1” cabbage, when grafted onto the two Chinese kale cultivars, did not formed flower buds. Flowering was successfully induced in “Watanabe-seiko No.1” by grafting onto three out of the seven tested radish cultivars, and in “Kinkei No.201” and “Red cabbage” by grafting onto one tested radish cultivar. In “Watanabe-seiko No.1,” the earliest flower bud appearance was observed at 29 days after grafting. Seeds were also obtained from the three cabbage cultivars that flowered by grafting. Gene expression analysis of “Watanabe-seiko No.1” cabbage scions which formed flower buds by grafting, revealed high expression of the homolog of the floral integrator, SUPPRESSOR OF OVEREXPRESSION OF CONSTANS 1 (BoSOC1), at the time of flower bud appearance. However, in the same leaf samples, we observed low expression of two homologs of florigen, FLOWERING LOCUS T (BoFT.C2 and BoFT.C6). In addition, two homologs of the floral repressor FLOWERING LOCUS C (BoFLC3 and BoFLC4), which are known to be down-regulated before flower bud differentiation in the vernalization pathway, were highly expressed, indicating that grafting onto radish induces cabbage flowering independently of the vernalization pathway. The expression level of the radish FT homolog (RsFT) in “Rat's tail-G2,” which had highly induced flowering in the grafted cabbage scion, was higher than in the other radish cultivars. However, although “Rat's tail-CH” effectively induced flowering in the cabbage scion, the expression of RsFT was low in this cultivar. In this study, floral induction of non-vernalized cabbage cannot be explained by the expression levels of RsFT in rootstock plants, alone. The flowering of non-vernalized cabbage would be induced by transmissible agents from rootstocks and not by the expression of cabbage FT, BoFT, from the scion itself.